The Faedo-Galerkin Method for the Relativistic Boltzmann Equation - Ayissi, Raoul Domingo; Noutchegueme, Norbert (Communications in Mathematics and Applications, 2013)
We prove the existence and uniqueness of solution to the relativistic Boltzmann equation locally in time. We clarify the choice of the function spaces and we establish step by step all the essential energy estimations leading to the existence theorem.